A Ópera do Malandro como documento histórico para análise do conceito de malandragem em Chico Buarque - Santos, Tiago Xavier dos (2010)
The objective of this work is the analyses of the concept of malandragem on Ópera do Malandro of Chico Buarque on it s historical and literature components. In first place, it´s was made a survey of the malandro s path on the Brazilian society, from the origins till it´s transformation on the Vargas Era, using the Anthropology, Sociology and literature studies. After than, it´s was made an analyses of the Ópera structure, connecting to the historical context in which was produced and the critics that make to that context. At last, it was selected some songs that wasn t from the opera itself, but it´s part of the Chico Buarque s songbook, functioning as a documental support for the understanding of the malandragem concept present in his work. To make this analyses, it was start from the exam of the verbal text of the songs searching for meaning that may be unspoken. We conclude that the analyses of this linked structure elements allowed to explicit aspects of the historical context and of the fictional creations which wasn t elucidated by the storyline.